STARTEGI PEMASARAN RESTORAN ORCHID BUNGALOW - Yayuk Yuliana (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
The purpose of this study was to determine the strategy of marketing implementation in orchid bungalow ecotourism accommodation and restaurant services in Bahorok District, Langkat Regency, North Sumatra Province in an effort to maintain visitor loyalty. The research method used in this study is descriptive research with a qualitative approach. The results showed that the strategy of implementing relationship marketing in orchid lodging and restaurant services for frog ecotourism bungalows in maintaining visitor loyalty, namely by prioritizing customer satisfaction, effective communication with visitors, achieving mutual goals that are mutually beneficial, and paying attention to the quality of services and facilities of service providers . As a result, until now the frog orchid bungalows have visitors who are loyal to orchid frog stone bungalows. These visitors come from domestic and foreign tourists.